(untitled) (Cardiovascular Journal, 2024)
During the realm of cardiovascular health, where disease remains strong, cardiopulmonary bypass (CPB) is a crucial tool in surgical interventions. Navigating through CPB and the turbulent waters of shock can unveil a difficult opponent called vasoplegia. Despite the heart’s efforts to maintain its rhythm, the body may experience a state of low systemic vascular resistance, a key feature of vasoplegia. Physicians commonly resort to vasopressor medications to fight this condition, however, vasoplegia’s subtle nature can resist these efforts, leading to catecholamines resistance and increased risks of mortality. To tackle this issue, the medical field has introduced new treatment options such as angiotensin II, a non-catecholamine vasopressor, and nitric oxide scavengers, providing hope for vasoplegia management. Our investigation explores the characteristics, risk factors, and pathophysiology of vasoplegia. Vasoplegic syndrome typically occurs after cardiothoracic surgery, causing high-output shock with compromised systemic vascular resistance. The syndrome’s core lies in the dysregulation of vasoconstriction and vasodilation in smooth muscle cells, influenced by various mechanical and patient-specific factors. A promising advancement is the emergence of catecholamine-sparing agents, showing potential in managing vasoplegia. Recent accounts suggest new treatment strategies, highlighting the need for large-scale clinical trials to validate findings and establish optimal management approaches. The ongoing fight against vasoplegia provides hope for improved outcomes in cardiovascular care as discoveries shape the field. Cardiovasc j 2024; 16(2): 92-97